(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to describe the current health status and disease burden among workers at plastic material manufacturing companies in Hung Yen in 2024. Methods: A cross-sectional descriptive study was conducted on 853 workers at plastic material manufacturing companies in Hung Yen. Data were collected retrospectively from the workers’ health records in 2024. Results: Most workers were male (78.8%) and aged 30–39 years (39.3%). The rate of underweight workers was 6.9%, while overweight and obesity accounted for 40.9%. Workers with good health status (type I and II) made up 70.4%, whereas poor health status (type IV and V) accounted for 7.3% and 0.8%, respectively. The most common diseases were digestive disorders (53.5%), ear-nose-throat diseases (49.5%), and endocrine disorders (49.5%). Workers with two diseases accounted for the highest proportion (30.7%), with a significant difference in disease number between males and females (p<0.05). Male sex and age over 50 years were significantly associated with poor health status and disease outcomes (p<0.05). Overweight and obese workers had a higher risk of having three or more concurrent diseases (p<0.05). Conclusion: The health status of workers in plastic material manufacturing companies in Hung Yen is unsatisfactory. High prevalences of digestive, ear–nose–throat, and endocrine disorders, poor health status, and multimorbidity were observed, with markedly poorer health outcomes among male workers, those aged over 50 years, and those who were overweight or obese.